2021
DOI: 10.1111/imb.12710
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile hormone regulates the reproductive diapause through Methoprene‐tolerant gene in Galeruca daurica

Abstract: Juvenile hormone (JH) signalling plays an important role in regulation of reproductive diapause in insects. However, its underlying molecular mechanism has been unclear. Methoprene‐tolerant (Met), as a universal JH receptor, is involved in JH action. To gain some insight into its function in the reproductive diapause of Galeruca daurica, a serious pest on the Inner Mongolia grasslands undergoing obligatory summer diapause at the adult stage, we cloned the complete open‐reading frame (ORF) sequences of Met and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…In this study, we found that depleting FoxO delayed the entry of G. daurica adults into diapause. The same result has been obtained after methoprene injections (Ma et al ., 2021a). These results indicate that FoxO plays an important role in regulating reproductive diapause in G. daurica .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we found that depleting FoxO delayed the entry of G. daurica adults into diapause. The same result has been obtained after methoprene injections (Ma et al ., 2021a). These results indicate that FoxO plays an important role in regulating reproductive diapause in G. daurica .…”
Section: Discussionmentioning
confidence: 99%
“…The G. daurica larvae were collected in May, 2021 from the Xianghuang Banner grasslands of Inner Mongolia, China, and they were reared on Allium mongolicum under natural conditions as described by Ma et al . (2021a). For the expression profiling, female adult samples were collected at 1, 3, 7, 10, 15, 25, 40, 60, 80, and 100 d posteclosion and the samples were maintained at −80 °C until RNA was extracted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methoprene-tolerant (Met) is a universal JH receptor. Silencing GdMet inhibits the expression of JHE and Vg , causing reproductive diapause of Galeruca daurica ( Ma et al, 2021 ). Adenylyl cyclase (AC) plays a role in cell signaling processes.…”
Section: Discussionmentioning
confidence: 99%
“…Galeruca daurica (Coleoptera: Chrysomelidae), a serious grassland pest since its sudden outbreaks on the Inner Mongolia grasslands in 2009 ( Zhou et al, 2016 , Zhou et al, 2019 ), has continually spread and caused great losses to pasture on the Inner Mongolia grasslands ( Ma et al, 2019 , Ma et al, 2021 ), and levels of damage has increased year by year ( Duan et al, 2022 ). The application of traditional chemical insecticides to control outbreaking pests in desert steppes has the advantages of a good insecticidal effect with rapid results, especially organophosphorus, pyrethroids, chloronicotinyl insecticide ( Dong et al, 2016 ; Gao et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%